Enhanced digital rights management authentication scheme based on smart card. Issue 3 (1st September 2013) - Yang, Hung‐Wen; Yang, Chou‐Chen; Lin, Woei
Abstract : As a result of the explosive growth in development for computer networks and information technologies in recent years, various activities take place on the Internet, such as the multimedia services. Today, the distribution of large scale digital content (such as audio, video and images) has become easier and more efficient than ever before. However, the intellectual property violation of copyright‐protected content has emerged as a major concern. Therefore digital contents are generally encrypted to prevent unauthorised access. A technology of digital rights management (DRM) refers to any of several encryption technologies used to protect digital contents against unauthorised copying, and to control the distribution of the content. Recently, Zhang et al . proposed a DRM authentication scheme based on smart card to realise session key exchange and mutual authentication among all the parties in DRM environment. The proposed scheme is efficient at server side and compact in smart card design. However, the authors will show their proposed scheme cannot resist insider attack and stolen smart card attack, then the authors will propose an improved scheme to preclude above weaknesses.